MODELS OF RAT SKIN WOUND HEALING: AN OVERVIEW - PANDEY, RATNANJALI; KUMAR GUPTA, RAMESH (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Wounds have developed into one of the earliest types of human pain, with two histories that go back to before the existence of humans. The growth of medical research led to an abundance of new ideas and opened the doors for creating a separate field solely dedicated to treating wounds. The underlying cause, the site of the injury, the mechanism of injury-producing symptoms, the depth and tissue loss of the wound, or the clinical presentation can all be used to categorize wounds. According to studies utilizing animal models, there are four stages of acute wound healing. It is a given that chronic wounds must go through similar underlying mechanisms. Hemostasis, inflammation, proliferation or granulation, and remodeling or maturation are adequate stages of wound healing. There has been a substantial change in how we understand and apply information. This study investigated every aspect of wound healing, including every pathway and model for wound healing.